Preclinical evaluation of Versius, an innovative device for use in robot-assisted thoracic surgery. (12th April 2022) - Aresu, Giuseppe; Dunning, Joel; Routledge, Tom; Bagan, Patrick; Slack, Mark
Abstract: OBJECTIVES: The adoption of robot-assisted thoracic surgery (RATS) has helped to overcome some of the challenges associated with surgeons performing conventional video-assisted thoracic surgery. The Versius Surgical System (CMR Surgical, Cambridge, UK) has been developed iteratively in line with surgical team feedback to improve the surgeon's experience and patient outcomes. The goal of this study was to assess the use of the device in RATS in a preclinical setting and to fulfil Idea, Development, Exploration, Assessment, Long-Term Follow Up–Devices stage 1 (Idea). METHODS: Four cadaveric sessions were conducted between November 2018 and December 2020, during which device performance in a range of thoracic operations was assessed. Procedures were categorized as either completed or not completed, and surgeons evaluated the device's ability to successfully complete necessary surgical steps. Port and bedside unit positions were recorded. RESULTS: In total, 22/24 (91.7%) thoracic procedures were successfully completed, including 17/18 lobectomies, 2/3 thymectomies and 3/3 diaphragm plications, in 9 cadaver specimens. One thymectomy could not be completed due to cadaver anatomy and 1 lobectomy was not completed due a console system fault. Port and bedside unit configurations were successfully validated for all procedures, and lead surgeons deemed the device to be well-suited for thoracic surgery. CONCLUSIONS: This preclinical study demonstrated the successful use of the device in RATS in cadaveric models and supports progression to small-scale clinical studies, as part of Idea, Development, Exploration, Assessment, Long-Term Follow Up–Devices stage 2a (Development). Abstract : Video-assisted thoracic surgery (VATS) is increasingly used to perform thoracic procedures that previously required a thoracotomy, including lobectomy, thymectomy and diaphragm plication [1–3].